The impact of Covid-19 restrictions on TB diagnosis in the City of Cape Town, South Africa - Dane, Pierre (Department of Public Health and Family Medicine, 2024)
Background: The first case of Covid-19 in South Africa was diagnosed on the 5h March 2020 and a national alert system based on perceived Covid-19 spread and the level of health system readiness and capacity was implemented. Varying levels of lockdown restriction were mandated, from ‘full shelter in place' (alert level 5) to minimal restrictions on social gatherings and mask-wearing (alert level 1). South Africa subsequently experienced 5 Covid- 19 waves with 14 changes to alert levels. Significant reductions in recorded new tuberculosis diagnoses and tuberculosis mortality were observed during the Covid-19 pandemic. We describe and quantify effects of the Covid-19 pandemic on new tuberculosis diagnosis in Cape Town. Methods: A time-series analysis was undertaken using routine data collected between 2018 and 2021 by the Western Cape Department of Health in the City of Cape Town. There were 87 621 tuberculosis episodes identified in 82 197 adult individuals. A multiple linear regression model was used to assess the relationship between the outcome daily counts of new tuberculosis diagnoses and independent variables alert level, the month of year to model seasonality of tuberculosis incidence, and the level of Covid-19 admission pressure as a proxy for pressure on the health services. Data were stratified according to their origin in primary health care and hospital settings, and further exploratory analysis assessed the effects of additional baseline population characteristics on the measured outcome. Results: Across all facilities, increasing severity of lockdown restrictions had a significant, increasing impact on reduction in number of new tuberculosis diagnoses. During alert level 4, the number of daily new diagnoses reduced from pre-pandemic levels by approximately 50% (β=-20, 95% CI:-22, -17). In the stratified analysis, alert level 4 reduced daily new tuberculosis diagnosis at primary health care facilities by 80% (β=-20, 95% CI:-22,-17) and at hospital facilities by only 11% (β=-1.6, 95% CI:-2.8,-1.4). Further analysis ruled out effects from independent baseline population characteristics including age, sex and comorbidities. Conclusions: Severity of Covid-19 restrictions had greater effect on reduction of new tuberculosis diagnosis than increased intensity of Covid-19 waves. The reduction was more pronounced at primary health care facilities, indicating that access to, and services at these facilities most likely impacted number of tuberculosis diagnoses more profoundly than at hospitals, and the resulting decreased tuberculosis testing at these facilities was the most likely contributing factor to the reduction in recorded tuberculosis diagnosis rather than a reduction in actual incidence of tuberculosis.